1963
DOI: 10.1366/000370263789621105
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Fluorescence Analysis of the Light Elements in Rocks and Minerals

Abstract: Recent advances in the x-ray fluorescence analysis of the light elements offer the advantage of speed and an accuracy approaching that of wet chemical procedures In addition to Fe, Mn, Ti, Ca, and K, the elements P, Si, Al, and Mg, previously considered too light to be determined quantitatively, can now be included in the scheme of analysis X-ray fluorescence analysis of these light elements is primarily confined to layers close to the surface, with the attendant problems of particle size, mineralogic history,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1967
1967
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…Other subsamples were dried and disaggregated for chemical analyses. Total phosphorus was determined by the X-ray fluorescence method of Rose and Adler (1963). Schleicher and Kuhn (1970) have shown that values determined by this method are accurate within the limits of most analytical methods, The sam.…”
Section: Methodsmentioning
confidence: 99%
“…Other subsamples were dried and disaggregated for chemical analyses. Total phosphorus was determined by the X-ray fluorescence method of Rose and Adler (1963). Schleicher and Kuhn (1970) have shown that values determined by this method are accurate within the limits of most analytical methods, The sam.…”
Section: Methodsmentioning
confidence: 99%
“…Some laboratories are now using the X-ray fluorescence spectrography technique for the quantitative determination of metallic oxides in bauxite samples. This technique, which is similar to the one described by Rose, Adler, and Flanagan ( 1963) and Tertian, Fagot, and Jamey (1964), is both rapid and accurate when used by experienced personnel.…”
mentioning
confidence: 62%
“…Rose et al 26 provided mixed calibrating standards containing granite (G-1) and diabase (W-1) in varying proportions using 1 : 9 borate fusion. They also used National Bureau of Standards' samples (e.g.…”
Section: Extension Of Rock References' Calibrationmentioning
confidence: 99%